Alta frequência de portadores genitais de Leptospira sp. em ovelhas abatidas na região semiárida do nordeste brasileiro - Silva, A. F.; Farias, P. J. A.; Silva, M. L. C. R.; Araújo Júnior, J. P.; Malossi, C. D.; Ullmann, L. S.; Costa, D. F.; Higino, S. S. S.; Azevedo, S. S.; Alves, C. J. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2019)
Although some leptospirosis investigations performed in sheep have indicated their genital tract colonization, further studies are necessary to clarify the whole role of genital carriers in this species.